Entrepreneurial Experience and Performance : From the Aspect of Sustainable Growth of Enterprises - Peng, Huatao; Zhou, Chen; Liu, Yang (MDPI, 2020)
In the uncertain entrepreneurial ecosystem, scholarly knowledge is bounded by the sustainable growth of entrepreneurial enterprises. Moreover, there is a lack of consensus in academic circles on the relationship between entrepreneurial experience and entrepreneurial performance. In adopting the meta-analysis method, we found a significant relationship between entrepreneurial experience and entrepreneurial performance based on an investigation of 45 independent samples (N = 18,752). We also examined theoretically derived moderators of this relationship referring to firm age, industry condition and experience type to test whether the moderating effects can explain the inconsistent research results on the relationship between entrepreneurial experience and entrepreneurial performance. The relationship was stronger for the high-tech industry than for low-tech industry, for the early business stage than for late business stage and for start-up experience compared to management experience, work experience and industry experience. Our research findings are meaningful for practitioners to achieve sustainable growth by better preserving and coordinating entrepreneurial experience in a dynamic environment. Further, these findings are also important for future research to analyze the factors triggering the heterogeneity of entrepreneurial experience and to investigate the extent to which the start-up experience is more capable of promoting entrepreneurial performance.
Keywords: entrepreneurial experience; entrepreneurial performance; sustainable growth; meta-analysis; fi=Tuotantotalous|en=Industrial Management|